Investigation of vitamin D, vitamin B12 and ferritin levels in children receiving home health care services in southeastern Türkiye (Annals of Medical Research, 2023)
Aim: For proper nutrition of children followed by the Home Health Care (HHC) unit, a close follow-up is extremely important. Vitamin deficiencies are common in children in this group who need parental or caregiver-dependent nutrition. The purpose of this study conducted in Batman Province, was to investigate vitamin D, vitamin B12 and ferritin levels of individuals under 18 years of age who are followed by the HHC unit and continue their lives and treatments at home, except for emergencies.Materials and Methods: This study was derived from the files of 416 pediatric patients who were followed up in Batman Province HHC unit between January 1, 2022, and December 31, 2022. It was designed as a retrospective, single-center study evaluating 25-hydroxyvitamin D (OH) levels, vitamin B12 levels, ferritin levels, and demographic variables from individuals followed by HHC unit. The data were collected from the HHC unit’s files. IBM-SPSS version 24 was used for analysis.Results: The mean age of the 416 children receiving home health care services included in the study was 10.38±4.37 years. 234 (56.2%) of the participants were male and 182 (43.8%) were female. The 25(OH)D level was 18.47±5.41 ng/mL for all ages, and the ferritin level was 34.90 (33.08) ng/mL. The vitamin B12 level was 480.31±190.38 ng/L. The 25-OH-D vitamin levels of the children in the study were significantly low.Conclusion: Patients followed within the scope of home health care services are at risk for malnutrition and vitamin deficiencies, and annual follow-up of the patients in this regard and personalized diet programs should be created. Vitamin D insufficiency and deficiency are common in children in this group, who cannot leave the house except for compulsory situations and cannot benefit from sunlight sufficiently. We think that these children with chronic diseases should take vitamin D prophylaxis.
Keywords: Home health care; Vitamin D; Vitamin B12; Ferritin; Children